ผลของการเตรียมตัวอย่างเบื้องต้นต่อการเปลี่ยนแปลงคุณภาพของผลิตภัณฑ์สะตออบแห้ง (EFFECT OF PRETREATMENTS ON THE QUALITY OF DEHYDRATED PARKIA SPECIOSE) - เทพนวล, รวงนลิน; เรืองวัชรินทร, อุราภรณ์; จันทโร, พราวตา; เจือมณี, อรุโณทัย; ทวีโรจนการ, ศิริพร (Srinakharinwirot University Journal of Sciences and Technology, 2020)
The drying process caused a significant changing in the chemical-physical properties of drying products. Therefore, the purpose of this study was to evaluate the effect of drying process and pretreatments on the physiochemical properties of dried Parkia speciosa seeds. Seeds of Parkia speciosa were dried in cabinet tray drier at three different temperatures (50, 60 and 70°C). Physicochemical and sensory qualities of dried Parkia speciosa were determined and compared with the control sample. Moisture content of Parkia speciosa seeds decreased with drying temperatures, whereas rehydration ratio increased. When compared with the unblanched treatment, drying the blanched Parkia Speciosa seeds at 70°C was the most pronounced factors affecting moisture content, dehydration ratio and colour degradation. The lowest moisture content of 6.55% was found in sample dried at 70°C. Less browning from drying was observed in blanched samples, which were dehydrated at 60°C. It was found that the proper condition for drying temperature was dried at 60°C for 5 hrs as considered from the sensory evaluation. Prior to drying at 60°C, fresh Parkia Speciosa seeds were blanched in hot water at 85°C for 15s and pre-treated with calcium chloride (CaCl2) and sodium chloride (NaCl) solution (0, 1, 1.5 and 2 % w/w) for 5 min at 27°C. Dried seeds without pretreatment was considered control sample. Pretreatment seeds with CaCl2 and NaCl solution induced similar changes of physicochemical properties of dried Parkia speciosa. All pretreated samples were acceptable when sensory qualities were evaluated. The most acceptable sample was Parkia speciosa seeds pretreated with 1% CaCl2 and dried at 60°C. Therefore, the blanching pretreatment prior to drying Parkia speciosa seeds results in sensory properties.